Antennas Performance Comparison of Multi-Bands for Optimal Outdoor and Indoor Environments Wireless Coverage - Karrar Shakir Muttair; Ali Z. Ghazi Zahid; Oras A. Shareef Al-Ani; Ahmed Mohammed Q. AL-Asadi; Mahmood F. Mosleh (IAES Indonesian Section, 2021)
This paper aims to implement a wireless Wi-Fi network (Indoor and Outdoor) in order to cover the environment of the Oxford Institute (to learn languages and computer skills) in the best methods and lowest cost in order to provide Wi-Fi service for faculty members and all members of the administrative board and students. The realistic three-floor indoor and outdoor environments of the Institute were designed with Wireless InSite Package (WIP). In addition, emphasis was focus on the use of two types of transmitting devices (Directional and Omni-Directional). The aim of using these two devices is to determine which device is better to cover the Institute's environment well. In this work, a different frequency bands scenario was used to determine which band is suitable for coverage and stability of the wireless network. These bands are S-Band (2.4GHz), C-Band (5GHz), C-Band (10GHz), Ku-Band (15GHz), Ka-Band (28GHz), and MmWave (39GHz). Moreover, the focus has been on the most important basic parameters to determine the performance level of the two devices (Directional and Omni-Directional) as well as to determine the performance level of the wireless network. The most important of these parameters are Path Losses (LPath), Path Gain (GPath), Received Signal Strength (RSS), Strongest Received Power, Coverage Ratio (CR), and Received Signal Quality Ratio (RSQR). According to the results that emerged, it was observed that Omni-Directional antennas are much better than Directional antennas, especially in NLOS (None-Line-of-Sight) regions. It was also noted that CR, LPath, and RSS at S-Band (2.4GHz) are much better than the rest of the bands, so that the CR and the RSQR at this band reach 83.2184% and 95.7383%, respectively. While at the MmWave-Band (39GHz), it reaches 31.0345% and 70.7937% respectively.